Activation enthalpies and entropies of the atropisomerization of substituted butyl-bridged biphenyls. Issue 17 (7th May 2015) - Bihlmeier, Angela; Rotzler, Jürgen; Rickhaus, Michel; Mayor, Marcel; Klopper, Wim
<x xml:space="preserve">Abstract</x> Contradictory results for activation enthalpies and entropies are obtained from HPLC, CD and DFT while the atropisomerization energies are similar.